2013
DOI: 10.1016/j.breast.2012.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Gene copy number variations in breast cancer of Sub-Saharan African women

Abstract: The goal of this study was CGH array profiling of breast cancer from Malian women in order to define differences with those from USA. CGH array was performed in 28 samples, 17 with a triple negative phenotype. The profiles were compared to those of 106 tumors from USA. 6 chromosomal regions (6p21, 9q34, 11q13, 12q24, 17q25 and 22q12.1-22q13.1) were identified with a significant higher rate of copy number alterations. These regions contain several genes of interest including BCR. FISH and IHC confirmed that BCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Breast cancer mortality rate is much higher among sub-Saharan women as compared to women in western countries, even though the incidence is much higher in western women [17] [18]. Five-year relative survival rates, standardised to the International Cancer Survival Standard [19], were calculated for patients aged 15 -99 years diagnosed during the year 1990-1994.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer mortality rate is much higher among sub-Saharan women as compared to women in western countries, even though the incidence is much higher in western women [17] [18]. Five-year relative survival rates, standardised to the International Cancer Survival Standard [19], were calculated for patients aged 15 -99 years diagnosed during the year 1990-1994.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study comparing breast cancer samples from African and American women has identified 6 chromosomal regions with a higher rate of CNAs and several candidate biomarkers that could be specific to African women [66]. …”
Section: Introductionmentioning
confidence: 99%
“…The majority of the studies assessing these alterations, in addition to their gene and epigenetic expression profiles, are in White European and African American patients with breast cancer (35,(40)(41)(42)(43)(44)(45). Few studies have been performed in patients from Sub-Saharan countries (24,25). Thus, the consequences of CNAs due to the genetic instability of their tumor types remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Among the African countries, SA has the highest number of published genomic research studies (assessed between 2004-2013), however only 6.1% of these studies are associated with cancer (20). To the best of our knowledge, few breast cancer studies have characterized patient genomic profiles and/or specific molecular alterations in their populations (14,(21)(22)(23)(24)(25). As a consequence, there is limited knowledge on their tumor biology and the corresponding lack of clinically relevant biomarkers that would be particularly beneficial for the prognosis and treatment of patients with breast cancer representative of the diverse racial groups of SA.…”
Section: Patterns Of Copy Number Alterations In Primary Breastmentioning
confidence: 99%